Mapping ultra-processed foods (UPFs) in India: a formative research study - Suparna Ghosh-Jerath; Neha Khandpur; Gaurika Kumar; Sahiba Kohli; Meenu Singh; Inderdeep Kaur Bhamra; Fernanda H Marrocos-Leite; K Srinath Reddy (BMC, 2024)
Abstract Background Increased consumption of ultra-processed foods (UPFs) which have additives such as artificial colours, flavours and are usually high in salt, sugar, fats and specific preservatives, are associated with diet-related non-communicable diseases (NCDs). In India, there are no standard criteria for identifying UPFs using a classification system based on extent and purpose of industrial processing. Scientific literature on dietary intake of foods among Indian consumers classifies foods as unhealthy based on presence of excessive amounts of specific nutrients which makes it difficult to distinguish UPFs from other commercially available processed foods. Methods A literature review followed by an online grocery retailer scan for food label reading was conducted to map the types of UPFs in Indian food market and scrutinize their ingredient list for the presence of ultra-processed ingredients. All UPFs identified were randomly listed and then grouped into categories, followed by saliency analysis to understand preferred UPFs by consumers. Indian UPF categories were then finalized to inform a UPF screener. Results A lack of application of a uniform definition for UPFs in India was observed; hence descriptors such as junk-foods, fast-foods, ready-to-eat foods, instant-foods, processed-foods, packaged-foods, high-fat-sugar-and-salt foods were used for denoting UPFs. After initial scanning of such foods reported in literature based on standard definition of UPFs, an online grocery retailer scan of food labels for 375 brands (atleast 3 brands for each food item) confirmed 81 food items as UPFs. A range of packaged traditional recipes were also found to have UPF ingredients. Twenty three categories of UPFs were then developed and subjected to saliency analysis. Breads, chips and sugar-sweetened beverages (e.g. sodas and cold-drinks) were the most preferred UPFs while frozen ready-to-eat/cook foods (e.g. chicken nuggets and frozen kebabs) were least preferred. Conclusion India needs to systematically apply a food classification system and define Indian food categories based on the level of industrial processing. Mapping of UPFs is the first step towards development of a quick screener that would generate UPF consumption data to inform clear policy guidelines and regulations around UPFs and address their impact on NCDs.